Konsep Manusia Al-Basyar dan Hubungannya dengan Pendidikan Islam - Eliyatul Fitriyah; Erdiyani, Fenny; Kamilia, Dina (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2025)
This study aims to examine the concept of Al-Basyar in the Qur'anic context and its implications for Islamic education, focusing on how human physical and spiritual dimensions are integrated into learning. The research employs a qualitative approach through a literature review, analyzing relevant books, journal articles, and Islamic texts to explore the theoretical and practical aspects of Al-Basyar in educational settings. The findings reveal that Islamic education grounded in the Al-Basyar concept emphasizes a balanced development of students’ physical and spiritual aspects. Educators are encouraged to create learning environments that nurture both physical well-being and mental health, while curricula and assessment systems should holistically integrate moral values and Islamic health education. This approach enables students to develop not only cognitive intelligence but also ethical awareness, physical vitality, and spiritual resilience. The study highlights the crucial role of teachers in modeling healthy behaviors, guiding students’ personal growth, and collaborating with parents to reinforce moral and spiritual education. By applying the Al-Basyar framework, Islamic education can effectively produce generations who are knowledgeable, morally upright, and capable of contributing positively to society.